Vantagem de custo de transação na criação de capital social em empresas de construção civil: uma abordagem relacional - Krainer, Jefferson Augusto (2021)
A construction company is able to achieve economic and social benefits through the integration of its suppliers. After all, this integration, if successful, has the potential not only to increase the construction company’s social capital (benevolence manufactured in social relations), but also to reduce its transaction costs. This study aims to model the relationships between supplier integration, social capital and transaction cost advantage in construction companies. The social capital and transaction cost theories are jointly applied to hypothesize that supplier integration leads to an increase in social capital and a transaction cost advantage and that the increase in social capital also results in transaction cost advantage. A survey provided participants with a self-administered electronic questionnaire, with responses recorded in the cloud. A total of 111 companies returned to the survey’s appeal. Structural equation modeling based on partial least squares, the acronym in English: PLS-SEM, was used to estimate the hypothesized relationships. The results indicate that the construction companies, when investing in supplier integration, are able to positively impact their social capital. The increase in social capital also reflects positively on the transaction cost advantage, including mediating the effect of supplier integration on the transaction cost advantage. The benefits of supplier integration are realized only through the development of social capital. The broader, more intense and diversified the supplier’s integration, the greater the accumulation of social capital and, consequently, the lower the transaction cost. Thus, instead of spending considerable resources to protect itself against the risks of exchange, a construction company can save on transaction costs by making sure that social capital accumulation is effective. The model developed is suitable for builders of any size, age of foundation and who have or have not signed a formal contract with their suppliers, even regardless of the length of relationship with them.